The communicative ability of UiTM Sarawak graduating students: focussing on grammatical accuracy / Simon Philip Botley @ Faisal Hakim … [et al.] - Simon, Philip Botley @ Faisal Hakim; Wan Hassan, Sharifah Zakiah; Rahim, Mahdalela (2015)
This study will explore Universiti Teknologi MARA (UiTM) Sarawak graduating students' oral proficiency, focusing on grammatical accuracy. Oral proficiency in English has always been the benchmark of language proficiency, and in the context of UiTM's language teaching curriculum, efforts to enhance students' oral proficiency are implemented through various language proficiency-based and English Language courses. A small corpus of group discussions from final semester Bachelor degree students in UITM Sarawak will be analysed to identify and classify grammatical errors and other performance factors in students' oral communication. The mini-corpus that will arise from this research will comprise at least 10 oral discussion transcripts, or as many transcripts as there are groups, depending on student numbers. As far as possible, the groups will be selected from a wide range of different faculties and disciplines represented at the UiTM Sarawak Samarahan campus.